AGRICULTURAL ADAPTATION AND MITIGATION DIRECTIVE STRATEGIES SUSTAINABLE IN INDONESIA - Sara, Dem Vi -; Maharani, Maya Dewi Dyah (Universitas Wahid Hasyim, 2022)
The formulation of the Strategy Directive for Sustainable Agriculture Mitigation and Adaptation in Indonesia is very useful in the preparation of innovation, research and development of agricultural affairs, as well as input for the Long-term Development Plan (RPJP) document. This paper examines the formulation of the strategy through research using the Multi Dimentional Scaling (MDS) analysis method by mapping perceptions (perceptual mapping) that relies on Euclidian Distance between one dimension and another. The results of the MDS analysis followed by the Analytical Hierarchy Process (AHP) analysis resulted in the formulation of a directive strategy for farmer empowerment through low carbon agricultural technology (Low Carbon) for climate mitigation efforts with a score of 0.201. These results can be used to determine agricultural programs and activities that are effective and efficient and able to anticipate disasters.Keywords: Sustainability, Mitigation, Adaptation, Agriculture, MDS, AHP.